Topical cutaneous application of CO(2) accelerates bone healing in a rat femoral defect model - Kuroiwa, Yu (BMC Musculoskelet Disord, 2019)
BACKGROUND: Bone defects may occur because of severe trauma, nonunion, infection, or tumor resection. However, treatments for bone defects are often difficult and have not been fully established yet. We previously designed an efficient system of topical cutaneous application of carbon dioxide (CO(2)) using a novel hydrogel, which facilitates CO(2) absorption through the skin into the deep area within a limb. In this study, the effect of topical cutaneous application of CO(2) on bone healing was investigated using a rat femoral defect model. METHODS: In this basic research study, an in vivo bone defect model, fixed with an external fixator, was created using a rat femur. The affected limb was shaved, and CO(2) was applied for 20 min/day, 5 days/week. In the control animals, CO(2) gas was replaced with air. Radiographic, histological, biomechanical, and genetic assessments were performed to evaluate bone healing. RESULTS: Radiographically, bone healing rate was significantly higher in the CO(2) group than in the control group at 4 weeks (18.2% vs. 72.7%). The degree of bone healing scored using the histopathological Allen grading system was significantly higher in the CO(2) group than in the control group at 2 weeks (1.389 ± 0.334 vs. 1.944 ± 0.375). The ultimate stress, extrinsic stiffness, and failure energy were significantly greater in the CO(2) group than in the control group at 4 weeks (3.2 ± 0.8% vs. 38.1 ± 4.8%, 0.6 ± 0.3% vs. 41.5 ± 12.2%, 2.6 ± 0.8% vs. 24.7 ± 5.9%, respectively.). The volumetric bone mineral density of the callus in micro-computed tomography analysis was significantly higher in the CO(2) group than in the control group at 4 weeks (180.9 ± 43.0 mg/cm(3) vs. 247.9 ± 49.9 mg/cm(3)). Gene expression of vascular endothelial growth factor in the CO(2) group was significantly greater than that in the control group at 3 weeks (0.617 ± 0.240 vs. 2.213 ± 0.387). CONCLUSIONS: Topical cutaneous application of CO(2) accelerated bone healing in a rat femoral defect model. CO(2) application can be a novel and useful therapy for accelerating bone healing in bone defects; further research on its efficacy in humans is warranted.